PERANCANGAN APLIKASI SISTEM INFORMASI LOKASI PARKIR BERBASIS ANDROID - Stevan Gerald Nathanael; Muhammad Yasser Arafat (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
The parking location is a temporary stop for vehicles and a very important facility in public places such as universities, trade centers, offices, airports, hotels and other public places. Important information for motorists in finding a parking location requires an application for the parking location information. The purpose of this application is to analyze and design an Android-based parking location information system application that can provide information on existing parking locations and can provide information on the amount of parking capacity available in the parking area. This application is designed for Android devices to make it easier for drivers to access information and save time. This research uses the waterfall method, this method has a sequential process, from analysis to support and can save time in the entire project phase can be achieved. The design method for analyzing the program uses the Unified Modeling Language (UML) with data storage in MySQL, uses the PHP programming language, and Android Studio as Android application development. The method used in system testing is black box testing and white box testing which is focused on software requirements. The benefits obtained in this parking location application system are to make it easier for users to find the desired parking location through an android device that can be accessed anywhere and anytime.